U-4: AN ANALYTICAL STUDY OF THE EXCERPTS OF TEN HADITHS MENTIONED IN "TAFSIR AL.MARAGHI" OF AHMAD BIN MUSTAFA AL.MARAGHI IN SURAH AL.MAIDA.: احمد بن مصطفیٰ المراغی کی تفسیر"المراغی"(سورۃ المائدہ) میں ذکرشدہ(۱۰) احادیث کی تخریج کاتجزیاتی مطالعہ - Amin Ullah; Muhammad Fakhar ul Din (International Journal of Islamic Business, Administration and Social Sciences (JIBAS), 2022)
The Qur’an is the last book of Allah Almighty, which has been revealed for the benefit and advice of mankind till the Day of Resurrection. Other heavenly books were for specific regions and specific nations and times.But the Qur’an is the book of all the nations that inhabit the earth. Therefore, Allah Almighty has made it perfect and complete in every respect and has bestowed innumerable qualities in it. Just as the last prophet has different characteristics compared to other prophets, so the book given to this prophet, the Quran and the Muhammadan Ummah also has many characteristics. Thousands of scholars and " Mufasserin" have written " Tafaseer" on the Qur’an in their own style. One of these contemporary "Mufasserin" is Ahmad ibn Mustafa al-Maraghi. He rely on the hadiths to support this. The following is a review of the hadiths mentioned under Surah Al-Ma’ida in his "Tafseer""Tafsir ul Almaraghi.